Seismic performance and fragility curves for reinforced concrete framed buildings in Klang Valley / Tan Kok Tong - Tan, Kok Tong (2016)
Fragility curves, nowadays are popularly used in earthquake engineering where structural damage due to complex earthquake can be described in terms of probability. In this study, two primarly objectives have been defined: (1) to conduct seismic response analyses and (2) to derive computational based fragility curves for reinforced concrete framed structures in Klang Valley. This study is solely based on computational efforts where a series of RC frmaed building are simulated. Reinforced concrete framed buildings of 3, 7 and 11 story have been selected. A four-story reinforced concrete school building with infill walls was also selected to be investigated. The simulation is based on force-based fiber elements for structural elements and a single equivalent diagonal strut is selected to model the infill walls. The simulation techniques were verified via comparison with shake table test results. This study performed nonlinear time history analyses via an open source OpenSees. Subsequently, fragility curves were generated with respect to PGA and 4 different damage states including slight damage state, moderate damage state, extensive damage state and complete damage levels. The structural damage was measured consistently with HAZUS definition of damage levels. The structural properties for the analyzed systems were selected to be determinate while the uncertainties associated with ground motions were considered to represent the inter-record variability. Finally, using constructed fragility curves, the degree of expected damage of the structures were estimated for expected earthquake magnitude. The seismic analysis shows that the presence of masonry infill walls was significant influence on the global response of the structure. Although the displacement of the structure with infill wall is reduced in the in-plane direction, it was increased in both in-plane and out-of-plane directions when the infill walls experienced loss in serviceability. It is also shown that the seismic fragility of the 3-story RC framed building is more relied on local site conditions than those of the 7- and 11-story RC framed buildings investigated.